Aquaporin 8ab is required in zebrafish embryonic intestine development - Wang, Shiping; Qin, Yinyin; Sheng, Jiajing; Duan, Xuchu; Shen, Lizong; Liu, Dong (Acta biochimica et biophysica Sinica, 2022)
The aquaporin 8 (AQP8) is a small integral membrane protein that selectively transports water and other small uncharged solutes across cell plasma membranes. It has been demonstrated that AQP8 is ubiquitously present in various tissues and organs of mammals, and participates in many physiological and pathological processes. Recent studies showed that AQP8 is highly expressed in the columnar epithelial cells of mammalian colonic mucosa facing lumen, indicating that AQP8 plays potential roles in the physiology and pathophysiology of gastrointestinal tract. However, the role of AQP8 during gastrointestinal tract development is unclear. In the present study, RT-PCR results reveal that the zebrafish genome encodes three kinds of ( , , and ). We use whole mount in situ hybridization to describe genes spatiotemporal expression pattern, and the results show that mRNA is detectable mainly in the zebrafish embryonic intestine. To reveal the details of distribution, histological sections are employed. Transverse sections indicate that mRNA expression is more intense in the layer lining the intestinal cavity. Knockout of using the CRISPR/Cas9 system induces intestine development defects and abnormal formation of intestinal lumen. In addition, mRNA significantly rescues the intestine defects in the mutant. These results indicate that is required in the intestine development of zebrafish.